AN AUTOIMMUNE POLYGLANDULAR SYNDROME TYPE II PRESENTING WITH HASHIMOTO’S THYROIDITS, DIABETES MELLITUS AND ADRENAL INSUFFICIENCY: A CASE REPORT - Caluscusin, Ivan Rommel; Barrera, Jerome (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Autoimmune Polyglandular Syndrome affects 2 or more endocrine glands. It is more commonly seen among females with a gender ratio of 3:1 and usually manifests at a peak age of between 20 and 60 years. Among the 3 subtypes, type 2 is the most frequent one, manifesting with autoimmune thyroiditis, Diabetes Melitus Type 1 and Addison’s disease. CASE We report a 40-year-old male who presented with multiple concomitant endocrine abnormalities. Physical and laboratory examinations revealed hyperthyroidism, diabetes mellitus and adrenal insufficiency. He was initially diagnosed with hyperthyroidism which eventually converted to hypothyroidism most likely Hashimoto’s thyroiditis, as evidenced by high TSH levels even after 1 month of discontinuing antithyroid medication. He was also discovered to have diabetes mellitus type 1 after initially being admitted for diabetic ketoacidosis. During his most recent admission for acute gastroenteritis, he came in hypotensive. ACTH stimulation test result was compatible with adrenocortical insufficiency. CONCLUSION A prompt diagnosis can prevent mortality and morbidity with this kind of syndrome. This can be treated individually by hormonal therapy.